Advice: Expanding the Communication Paradigm. Issue 1 (1st January 2015) - MacGeorge, Erina L.; Feng, Bo; Guntzviller, Lisa M.
Abstract : Advice is a ubiquitous form of support and influence, exchanged in diverse contexts. Communication scholars have examined how advice recipients evaluate advice, but have done less to explore the breadth of effects it can have. We contrast the "message paradigm" for advice research with three alternative paradigms, each developed primarily by scholars from other disciplines. We then spotlight five directions for future research, integrating elements of the alternative paradigms with communication questions, perspectives, and methods of inquiry. By acquainting our discipline with existing theory and research on advice, we encourage bolder exploration of this consequential interpersonal phenomenon.